Temporary childbirth migration and perinatal healthcare in rural Maharashtra, India - Rachel Murro; Alison M. El Ayadi; Rutuja Patil; Dhiraj Agarwal; Sanjay Juvekar; Juliana Kim; Nadia G. Diamond-Smith (Journal of Migration and Health)
Introduction: Maternal health in rural India has improved due to national initiatives, but inadequate healthcare provision persists across most sociodemographic groups. The connection between perinatal care and the widespread practice of Temporary Childbirth Migration (TCM)—returning to one's natal home for delivery and the postpartum period—remains unexplored. Methods: Cross-sectional data on migration and health visits were collected from a sample of 1288 women in the Vadu Health and Demographic Surveillance Site (HDSS) (Western Maharashtra) who gave birth in 2018–2022. Childbirth migration (exposure) was analyzed in three ways: binary (any migration), continuous (duration of stay), and multidimensional (duration of stay and change of provider). Outcomes included number of health visits – both facility check-ups and home visits by community health workers – and early antenatal care initiation. Multivariate poisson, negative binomial and logistic regressions were used. Sensitivity analyses checked for recall bias, the influence of migration distance, and model misspecification. Results: Migrators and non-migrators had similar outcomes in early antenatal care initiation, facility visits (before and after pregnancy), and prenatal community health worker visits. Migrators had fewer postnatal community health worker visits (IRR = 0.80; 95 % CI 0.70–0.92). Among migrators, longer natal village stays were associated with fewer community health worker visits in the prenatal period (IRR = 0.92; 95 % CI 0.88–0.96) but not postnatally (IRR = 1.03; 95 % CI 1.00–1.07). Women who switched to a new provider upon arriving in their natal village had fewer facility-based prenatal (IRR = 0.86; 95 % CI 0.78–0.96) but more postnatal visits (IRR = 1.41; 95 % CI 1.06–1.87), regardless of how long they stayed. Conclusion: For women who return to their natal home for childbirth, duration of stay and changing providers upon arrival are linked to differences in receipt of maternal healthcare. Increased attention to the needs of mobile women during the perinatal period is necessary to ensure they can participate in key birth customs while receiving adequate healthcare.